Youtube for Self-Regulated Language Learning: An EFL Perspective - Putri, Hj. Fadhilah Harahab (English Education: Jurnal Tadris Bahasa Inggris, 2019)
In the last few decades[N.K1] , self-regulated language learning has become topics of prime interest in education and important topic in educational research. Moreover in this digital era the technologies are growing rapidly. Technology-enhanced learning provides opportunities and fosters the development of SRL abilities. Hence, this study aims to investigate EFL university student’s use of YouTube as a tool or media for self-regulate their English learning. To reach the objective, a qualitative research method was used in this study. In this study, twelve participants were purposively selected because they were considered had experience of watching English videos on YouTube and could give sufficient information to answer the research question. Student’s questionnaire and interview are used to bring to light their perceptions of this self-directed language learning approach. Their responses were analyzed to provide insights towards learner’s perception toward this technology-enhanced learning. This research was still in the process of collecting data. The findings of this study were expected to provide an overview of the activity of learning English using YouTube could be beneficial to improve English skills. In addition, learning English through YouTube is considered to be more fun, interesting, and flexible than formal learning in the classroom. Through this research, educators and students were expected to be more aware of the benefits of using technology to learn English. So the quality teaching and learning improved.